Development of RT-PCR Assays for Simple Detection and Identification of Sabin Virus Contaminants in the Novel Oral Poliovirus Vaccines - Olga Singh; Hasmik Manukyan; Erman Tritama; Shwu-Maan Lee; Jerry P. Weir; Majid Laassri (Vaccines)
Background/Objectives: Conventional live oral poliovirus vaccines (OPVs) effectively prevent poliomyelitis. These vaccines are derived from three attenuated Sabin strains of poliovirus, which can revert within the first week of replication to a neurovirulent phenotype, leading to sporadic cases of vaccine-associated paralytic poliomyelitis (VAPP) among vaccinees and their contacts. A novel OPV2 vaccine (nOPV2) with enhanced genetic stability was developed recently; type 1 and type 3 nOPV strains were engineered using the nOPV2 genome as a backbone by replacing the capsid precursor polyprotein (P1) with that of Sabin strains type 1 and type 3, respectively. The nOPV vaccines have a high degree of sequence homology with the parental Sabin 2 genome, and some manufacturing facilities produce and store both Sabin OPV and nOPV. Therefore, detecting Sabin virus contaminations in nOPV lots is crucial. Methods: This study describes the development of pan quantitative reverse transcription polymerase chain reaction (panRT-PCR) and multiplex one-step RT-PCR (mosRT-PCR) assays for the straightforward detection and identification of contaminating Sabin viruses when present in significantly higher amounts of nOPV strains. Results: The two assays exhibit high specificity, reproducibility, and sensitivity to detect 0.0001% and 0.00001% of Sabin viruses in nOPV, respectively. Additionally, an analysis of 12 trivalent nOPV formulation lots using both methods confirmed that the nOPV lots were free from Sabin virus contamination. Conclusions: The results demonstrated that the RT-PCR assays are sensitive and specific. These assays are relevant for quality control and lot release of nOPV vaccines.